Novel Biophotonics Techniques and Applications V 2019
DOI: 10.1117/12.2526394
|View full text |Cite
|
Sign up to set email alerts
|

Influence of scattering and birefringence on the phase shift between electric field components of polarized light propagated through biological tissues

Abstract: Influence of scattering and birefringence on the phase shift between electric field components of polarized light propagated through biological tissues," Proc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…[19][20][21] Moreover, it has been demonstrated that utilizing circularly polarized light in frame of Stokes-vector polarimetry approach, complemented by the use of Poincaré sphere as a quantitative graphical tool, has a high potential for tissue characterization and evaluation of cancer aggressiveness. [22][23][24][25][26][27] In terms of optical properties, besides absorption, biological tissues are characterized by scattering (typically, in the order of tens of mm −1 for visible light) and high anisotropy of scattering (g ≈ 0.8). 28 In addition to scattering of light, due to heterogeneous fibrous structure, biological tissues often exhibit linear form birefringence, which is a measurable quantity; its changes may act as a metric for certain structural abnormalities of biological tissues.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Moreover, it has been demonstrated that utilizing circularly polarized light in frame of Stokes-vector polarimetry approach, complemented by the use of Poincaré sphere as a quantitative graphical tool, has a high potential for tissue characterization and evaluation of cancer aggressiveness. [22][23][24][25][26][27] In terms of optical properties, besides absorption, biological tissues are characterized by scattering (typically, in the order of tens of mm −1 for visible light) and high anisotropy of scattering (g ≈ 0.8). 28 In addition to scattering of light, due to heterogeneous fibrous structure, biological tissues often exhibit linear form birefringence, which is a measurable quantity; its changes may act as a metric for certain structural abnormalities of biological tissues.…”
Section: Introductionmentioning
confidence: 99%
“…For that end, we used a polarized light, controlled pressure, a video camera, and image processing. The use of crossed circular polarizers attenuates the reflection component of light captured by the digital camera, enabling visualization of deeper regions of the skin [38,39]. Our system produced successful measurements in subjects with dark skin (phototypes V and VI), which are a challenge for visual CRT measuring method [28,40,41], and has not been demonstrated by other studies.…”
Section: Discussionmentioning
confidence: 99%
“…In another study to be published elsewhere, we noticed that application of high pressure in the forearm (23kPa) increased noise, decreased fit quality, and repeatability. Our success with using low pressure (7 kPa) may be attributed not only to the higher sensitivity of digital cameras but also to the use of crossed circular polarizers, which improves SNR by attenuating the component due to reflection on the skin surface [36,38,39]. We believe that with adequate image processing for removal of reflection, the polarizers will be unnecessary.…”
Section: Discussionmentioning
confidence: 99%